Evaluation of the Usefuness of Youtube Videos as Sources Related to Vitrectomy in Vitreous Hemorrhage - Mehmet Çıtırık; Murat Serkan Songur (Genel Tıp Dergisi, 2022)
Objective: To evaluate the usefulness of YouTube videos about vitrectomy in vitreous hemorrhage surgery as a resource. Methods: The first 100 videos were evaluated when they were scanned by typing "vitreous hemorrhage vitrectomy" in the YouTube search engine. These videos were also analyzed and scored using DISCERN, Journal of the American Medical Association (JAMA) and Global Quality (GQ) scoring systems. Results: The DISCERN score of the evaluated videos was 37.2 ±6.5; JAMA score 1.9 ± 0.5; The GQ score was 2.0 ± 0.5. According to the results, vitrectomy in vitreous hemorrhage surgery videos, DISCERN score is weak; The JAMA score was evaluated as low quality and poor quality in the GQ score. Conclusion: Although there are enough videos on YouTube with vitrectomy in vitreous hemorrhage, its usefulness as a resource is low and its quality is poor.